Mycobiome characterization of “Ghimisone”, a Sardinian ancient barley sourdough traditionally used in Sardinia for making “Ogliathu” bread - Federico Lai; Angelica Lai; Roberta De Bellis; Davide Sisti; Lucia Potenza (Italian Journal of Mycology, 2022)
The sourdough is a biological complex matrix consisting of yeasts and lactic acid bacteria, derived from the spontaneous fermentation of the native microorganisms normally present in flour. In Italy, the microbiota of several hundred sourdoughs have been characterized at molecular and functional level and some of them have received the Protected Designation of Origin Annotation (PDO) or Protected Geographical Indication (PGI). Also in Sardinia, until the ‘50s, the barley carasau bread was produced using a sourdough named Ghimisone. The importance of keeping regional traditions alive and scientific curiosity have led to this work in which the mycobiota of Ghimisone was investigated for the first time. Three types of Ghimisones have been set up using flours of barley, naked barley, and a mixture of naked barley and “black lentil” of Calasetta. The mycobiota from these sourdoughs were investigated using independent molecular culture identification. Twenty different fungal species were found. The results were unexpected and showed that the mycobiome of Ghimisone is different from all other sourdoughs known in the literature. The diversity in the mycobiome of Ghimisone compared to known sourdoughs might suggests different nutritional and aromatic characteristics of its derived barley bread.